Simple Science Learning To Improve Children's Cognitive Abilities Through Taste Playing Activities - Yusnita, Novi Cynthia; Afdhalina, Afdhalina; Dinda Widyastika (Jurnal Scientia, 2024)
This research was motivated by children who rarely learn science because the activities carried out are not appropriate for early childhood. Science learning for young children is very important because it can build a strong foundation for their scientific understanding in the future. At an early age, the approach used in teaching science must be fun, interactive, and appropriate to the child's developmental stage. So the aim of this research is to find out the extent of children's cognitive abilities by carrying out simple science learning through play activities to get to know taste. The research method used in this research is a descriptive qualitative method, namely a method used to describe actual phenomena. To support this research, data was collected using observation, interviews and documentation. The results of this research are that there are five playing activities to get to know taste, namely exploring taste, matching taste, guessing taste, creating taste, and making a taste book. By doing these activities, young children not only learn about taste but also develop important cognitive skills such as problem solving, memory, and understanding concepts. Activities that involve this sense make science learning more interesting and interactive.